LOKUS KAWALAN SEBAGAI MODERATOR DALAM HUBUNGAN ANTARA PENGARUH RAKAN SEBAYA DAN SIKAP TERHADAP TINGKAH LAKU SEKSUAL DALAM KALANGAN REMAJA HAMIL LUAR NIKAH DI SEMENANJUNG MALAYSIA - SHAHRUDDIN, NOR JUMAWATON (Human Sustainability Procedia, 2018)
This study examined the moderating role of locus of control on the relationship between peer influence and attitude towards sexual behaviour. Based on correlation design, the sample of this study consisted of 204 teenagers out of wedlock in shelters and rehabilitation institutions in Peninsular Malaysia. Hypotheses were tested using bootstrapping analyses. Result revealed that a) peer influence and locus of control significantly related to attitude towards sexual behaviour; and b) locus of control moderated the influence of peer influence and attitude towards sexual behaviour. Accordingly, the study contributed to a better understanding of the attitude towards sexual behaviour among teenagers out of wedlock in the context of the impact of the social environment of teenagers, whether through external factors or internal factors. The findings also proved the current trend that teenagers are easily influenced by their peers through the aspects of behavior.This shows that the social status factor should be given serious attention and be taken into consideration in the development of intervention programs to prevent and avoid the phenomenon of teenage pregnancies outside marriage from becoming widespread